Structural and functional conservation of half-smooth tongue sole Cynoglossus semilaevis RIP3 in cell death signalling. Issue 82 (November 2018) - Ge, Yuan; Yang, Han; Zhao, Linan; Luo, Shaona; Zhang, Hengyu; Chen, Songlin
Abstract: Receptor interacting protein kinase 3 (RIP3) has emerged as an essential molecular regulator in human inflammation with accumulating evidence in vertebrates. However, the structure and functions of RIP3 in teleosts remains elusive. Here we identified one RIP3 homologue from half-smooth tongue sole Cynoglossus semilaevis, designated CsRIP3. The open reading frame (ORF) of CsRIP3 contained 1491 nucleotides and encoded a protein with 496 amino acids (Mw = 55.44 kDa). CsRIP3 expression was detected in various tissues in half-smooth tongue soles. CsRIP3 expression was up-regulated after pathogens i.e. Vibrio and poly (i:c) treatment in vivo, indicating its possible role in teleost immune response. Further analysis using human cells demonstrated that CsRIP3 exhibited highly conserved pro-apoptotic and pro-necroptotic functions in comparison with human RIP3. In conclusion, for the first time we reported the homologous structure and functions of CsRIP3 in inflammatory cell death, which provides novel perspectives on fish immunity studies in future. Highlights: Receptor Interacting Protein Kinase 3 (RIP3) cloned from half-smooth tongue sole Cynoglossus semilaevis was designated CsRIP3. CsRIP3 was upregulated in response to bacterial and viral challenges in different tissues in half-smooth tongue sole. CsRIP3 has conserved protein structure and performs homologous functions in cell death in comparison with mammal RIP3.